2013
DOI: 10.1371/journal.pone.0067845
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Selenium Deficiency Exacerbates DSS-Induced Epithelial Injury and AOM/DSS-Induced Tumorigenesis

Abstract: Selenium (Se) is an essential micronutrient that exerts its functions via selenoproteins. Little is known about the role of Se in inflammatory bowel disease (IBD). Epidemiological studies have inversely correlated nutritional Se status with IBD severity and colon cancer risk. Moreover, molecular studies have revealed that Se deficiency activates WNT signaling, a pathway essential to intestinal stem cell programs and pivotal to injury recovery processes in IBD that is also activated in inflammatory neoplastic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 76 publications
6
58
0
1
Order By: Relevance
“…Clinical studies have shown supplementation with Se in UC patients leads to symptomatic relief from active colitis (24). Furthermore, our studies demonstrating the need for selenoproteins to alleviate DSS-colitis are in agreement with a recent study demonstrating that decreased levels of dietary Se exacerbate DSS-colitis (5). More importantly, our studies implicate macrophage selenoproteins to be critical in resolution of injury.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Clinical studies have shown supplementation with Se in UC patients leads to symptomatic relief from active colitis (24). Furthermore, our studies demonstrating the need for selenoproteins to alleviate DSS-colitis are in agreement with a recent study demonstrating that decreased levels of dietary Se exacerbate DSS-colitis (5). More importantly, our studies implicate macrophage selenoproteins to be critical in resolution of injury.…”
Section: Discussionsupporting
confidence: 92%
“…Particularly in inflammatory bowel disease (IBD), decreased levels of Se are seen in IBD patients of ulcerative colitis (UC) or Crohn’s disease (24). Recent studies using a two-stage carcinogenesis model in mice demonstrated Se deficiency to exacerbate disease severity and colon cancer risk by enhanced epithelial injury (5). Previous studies from our laboratory have shown that Se through its incorporation into selenoproteins suppressed inflammation and decreased the production of tumor necrosis factor-α (TNFα) and prostaglandin E 2 (PGE 2 ) (6), which have also been shown to be elevated in the plasma of UC patients (7).…”
Section: Introductionmentioning
confidence: 99%
“…We found that SEPP1 truncation resulted in an increase in tumor number (7.9 ± 1.4 vs. 3.9 ± 0.7 tumors per mouse, P = 0.02; Figure 5B). We have previously determined that selenium deficiency results in increased dysplasia grade in this model (16). Similarly, tumor grade was more advanced in Sepp1 Δ240-361/Δ240-361 mice (P < 0.05; Figure 5C).…”
Section: Loss Of Sepp1 Enhances Both Tumor Promotion and Initiationsupporting
confidence: 53%
“…Several epidemiological studies have inversely correlated nutritional selenium status and cancer risk, particularly in colon cancer (15). Recently, our laboratory has demonstrated that selenium deficiency in mice exacerbates intestinal injury in response to chemical models of colitis and increases tumorigenesis in CAC modeling (16).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Indeed, previous studies from our laboratory have demonstrated that dietary selenium influences the severity of colitis and colitisassociated cancer (CAC) in mouse models. 4 The most abundant plasma selenoprotein is selenoprotein P (SEPP1). SEPP1 contains 10 selenocysteine residues and is essential for selenium transport and the production of other selenoproteins throughout the body.…”
mentioning
confidence: 99%